Software-defined connectivity in a mobile environment - Lopes, Inês Mariana Lemos (2020)
Broadband Internet access on trains has become an expected service for passengers, and the rise in quality demand has been posing a challenge to service providers. There are solutions for Internet access on trains that lack the flexibility and redundancy needed for an improved QoS in the network. Thus, this dissertation studies two new load balancing solutions, one distributed and the other centralized. In an emulated train network, routers of each car communicate their network statistics to other nodes of the network, to be used in load balancing decisions. In the distributed solution, each router has the capacity to make load balancing decisions, while in the centralized solution, an onboard controller makes those decisions. The latter solution is based on load balancing in an SDN environment. In this system, a remote entity aggregates the passengers’ traffic and forwards it to an external network, or to the Internet. The systems must provide an improved quality of experience to the passengers on the train and the total avaliable bandwidth should be distributed evenly by all cars. Requirements were established for the systems, which were developed after an in-depth analysis of solutions for Internet access on board found in the literature. After obtaining the results of the performance tests, it was concluded that the systems improve the QoE of the passengers, as long as the network conditions are approximately constant for an extended period.